The Design of a Detection Robot with OLED Display - Rachmat Anggi Marvianto; Rizky Gauraf; Yunus Bakhtiar Arafat; Zang Panpan (International Journal of Engineering Continuity, 2023)
OLED display has the advantages of self-illumination, wide viewing angle, fast response, small size, small weight, flexibility. It is a huge breakthrough in the field of display technology, and enhances the visual enjoyment and on-the-spot experience of people. With the rapid development of science and technology, the combination of OLED and robot has attracted attention from most of the fields. In this paper, the working principle, advantages and main application fields of OLED devices are introduced, and a detection robot with OLED is designed. The detection robot can accurately control the speed of the motor and the angle of the steering gear within a distance of 1,000 meters, and receive the images from airborne cameras in real time.